ANALISIS PERTUMBUHAN PENJUALAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP KINERJA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rina Milyati Yuniastuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
This research aims to determine the effect of partial sales growth on company performance, theinfluence of profitability on company performance and also the effect of liquidity on companyperformance and to know the simultaneous influence of sales growth, profitability and liquidity oncompany performance. which is listed on the Indonesian stock exchange. As for the results of this studyit turns out that both partially and simultaneously have an effect. This means that sales growth,profitability and liquidity have a very big role in the company's performance.